2021
DOI: 10.1002/jdd.12587
|View full text |Cite
|
Sign up to set email alerts
|

The scope of dental education during COVID‐19 pandemic: A systematic review

Abstract: Introduction COVID‐19 forced e‐learning processes to develop abruptly and posed challenges to the educational infrastructure. Emergency Remote Teaching was designated to distinguish the new educational scheme. This concept involves production of online activities that may return to face‐to‐face format as soon as the isolation period ends. Objective From March through September of 2020, this systematic review attempted to elucidate experiences, benefits, and challenges enforced in dental education due to the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
13

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 44 publications
(188 reference statements)
3
31
0
13
Order By: Relevance
“…A recent systematic review identified that the Zoom® platform was the preferred one among interviewees in studies included in this research [23]. Zoom® offers videoconferencing services for up to 1000 participants, with several possibilities, such as recordings, transcriptions, screen sharing, sending and receiving of files and chatting [24].…”
Section: From Face-to-face Teaching To the Use Of Digital Platforms: ...mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review identified that the Zoom® platform was the preferred one among interviewees in studies included in this research [23]. Zoom® offers videoconferencing services for up to 1000 participants, with several possibilities, such as recordings, transcriptions, screen sharing, sending and receiving of files and chatting [24].…”
Section: From Face-to-face Teaching To the Use Of Digital Platforms: ...mentioning
confidence: 99%
“…Reported difficulties included the limited knowledge of the teaching staff on technology, the availability and quality of students' connection to the internet [13,23,31], extra expenses for increasing internet franchise [13], inadequacy of some topics for the online version [23,41], lack of development of clinical skills and communication with patients [2], lack of attention on the part of students [13,31,40], lack of motivation and lack of adequate books or study material in their homes [31], the intensive nature of resources, student misbehavior [40], time management difficulties [31] and lack of electronic devices, especially in middle- [41] and low-income countries [46].…”
Section: Advantages and Limitations Of Online Educationmentioning
confidence: 99%
“…Reviews have also highlighted the challenges in migrating to remote education 11,12 which include poor knowledge of staff on how to deal with technology, poor internet connections and difficulty in transitioning content for online learning. 11,12 By contrast, some students and staff report satisfaction with remote learning, 2,13 especially when collaboration and engagement with peers is facilitated. 2 A preliminary search of repositories specific to COVID-19 literature identified several existing reviews of alternative education delivery strategies for medical and healthcare students during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Intraprofessional and interprofessional collaboration and teamwork through online modules were often imperative to facilitate and support the learning process and the exam system worldwide [22][23][24][25]. In this way, the learning process of technical skills and theoretical knowledge of dental subjects and the cultivation of ICS were accomplished at the same time by teamwork assignments [26].…”
Section: Introductionmentioning
confidence: 99%